A 4.6 Mb Inversion Leading to PCDH15-LINC00844 and BICC1-PCDH15 Fusion Transcripts as a New Pathogenic Mechanism Implicated in Usher Syndrome Type 1 - Vaché, Christel; Puechberty, Jacques; Faugère, Valérie; Darmaisin, Floriane; Liquori, Alessandro; Baux, David; Blanchet, Catherine; Garcia-Garcia, Gema; Meunier, Isabelle; Pellestor, Franck; Koenig, Michel; Roux, Anne-Françoise (Frontiers in Genetics, 2020)
Usher type 1 syndrome is a rare autosomal recessive disorder involving congenital severe-to-profound hearing loss, development of vision impairment in the first decade and severe balance difficulties. The PCDH15 gene, one of the five genes implicated in this disease, is involved in 8 to 20% of cases. In this study, we aimed to identify and characterize the two causal variants in a French patient with typical Usher syndrome clinical features. Massively parallel sequencing-based gene panel and screening for large rearrangements were used which detected a single multi-exon deletion in the PCDH15 gene. As the second pathogenic event was likely localized in the unscreened regions of the gene, PCDH15 transcripts from cultured nasal cells were analyzed and revealed a loss of junction between exon 13 and exon 14. This aberration could be explained by the identification of two fusion transcripts, PCDH15-LINC00844 and BICC1-PCDH15, originating from a 4.6 Mb inversion. This complex chromosomal rearrangement could not be detected by our diagnostic approach but was instead characterized by long-read sequencing, which offers the possibility of detecting balanced structural variants (SVs). This finding extends our knowledge of the mutational spectrum of the PCDH15 gene with the first ever identification of a large causal paracentric inversion of chromosome 10 and illustrates the utility of screening balanced SVs in an exhaustive molecular diagnostic approach.